Blunted perception of breathlessness in three cases of low grade insular-glioma - Chapman, Tom P.; Farrell, Sarah M.; Plaha, Puneet; Green, Alexander L.; Moosavi, Shakeeb H. (Frontiers in Neuroscience, 2024)
Better understanding of breathlessness perception addresses an unmet clinical need for more effective treatments for intractable dyspnoea, a prevalent symptom of multiple medical conditions. The insularcortex is predominantly activated in brain-imaging studies of dyspnoea, but its precise role remains unclear. We measured experimentally-induced hypercapnic air-hunger in three insular-glioma patients before and after surgical resection. Tests involved one-minute increments in inspired CO2, raising end-tidal PCO2 to 7.5mmHg above baseline (38.5±5.7mmHg), while ventilation was constrained (10.7±2.3l/min). Patients rated air-hunger on a visual analogue scale (VAS). Patients had lower stimulus-response (2.8±2 versus 11±4 %VAS/mmHg; p=0.004), but similar threshold (40.5±3.9 versus 43.2±5.1mmHg), compared to healthy individuals. Volunteered comments implicated diminished affective valence. After surgical resection; sensitivity increased in one patient, decreased in another, and other was unable to tolerate the ventilatory limit before any increase in inspired CO2.We suggest that functional insular-cortex is essential to register breathlessness unpleasantness and could be targeted with neuromodulation in chronically-breathless patients.Neurological patients with insula involvement should be monitored for blunted breathlessness to inform clinical management.